Proteome‐wide identification of S‐sulphenylated cysteines in Brassica napus. (15th August 2021) - Yu, Liangqian; Iqbal, Sidra; Zhang, Yuting; Zhang, Guofang; Ali, Usman; Lu, Shaoping; Yao, Xuan; Guo, Liang
Abstract: Deregulation of reduction–oxidation (redox) metabolism under environmental stresses results in enhanced production of intracellular reactive oxygen species (ROS), which ultimately leads to post‐translational modifications (PTMs) of responsive proteins. Redox PTMs play an important role in regulation of protein function and cellular signalling. By means of large‐scale redox proteomics, we studied reversible cysteine modification during the response to short‐term salt stress in Brassica napus ( B . napus). We applied an iodoacetyl tandem mass tags (iodoTMT)‐based proteomic approach to analyse the redox proteome of B. napus seedlings under control and salt‐stressed conditions. We identified 1, 821 sulphenylated sites in 912 proteins from all samples. A great number of sulphenylated proteins were predicted to localize to chloroplasts and cytoplasm and GO enrichment analysis of differentially sulphenylated proteins revealed that metabolic processes such as photosynthesis and glycolysis are enriched and enzymes are overrepresented. Redox‐sensitive sites in two enzymes were validated in vitro on recombinant proteins and they might affect the enzyme activity. This targeted approach contributes to the identification of the sulphenylated sites and proteins in B. napus subjected to salt stress and our study will improve our understanding of the molecular mechanisms underlying the redox regulation in response to salt stress. Abstract : ROS mediate post‐translational modifications of proteins by oxidation of cysteine residues. IodoTMT approach was employed to comprehensively identify the redox sensitive proteins in B. napus in response to salt stress, contributing to the understanding of redox‐based molecular changes prevailing in B. napus proteome subjected to salt stress.